2009
DOI: 10.4161/cc.8.6.7939
|View full text |Cite
|
Sign up to set email alerts
|

Viral subversion of immunogenic cell death

Abstract: While physiological cell death is non-immunogenic, pathogen induced cell death can be immunogenic and hence stimulate an immune response against antigens that derive from dying cells and are presented by dendritic cells (DCs). The obligate immunogenic "eat-me" signal generated by dying cells consists in the exposure of calreticulin (CRT) at the cell surface. This particular "eat-me" signal, which facilitates engulfment by DCs, can only be found on cells that succumb to immunogenic apoptosis, while it is not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 76 publications
1
54
0
1
Order By: Relevance
“…In accord with this speculation, there is ample evidence that pathogenic viruses can manipulate RIP3-dependent necroptosis, 57,58 perhaps as a strategy for immune escape. In this regard, it should be noted that viruses also subvert pathways linked to ICD including caspase-8 activation, 59 endoplasmic reticulum stress, 60 autophagy, 61 and type-1 IFN responses. 62 Successful anticancer chemotherapeutic agents induce all these hallmarks of ICD, suggesting that they induce a sort of 'viral mimicry'.…”
Section: Discussionmentioning
confidence: 99%
“…In accord with this speculation, there is ample evidence that pathogenic viruses can manipulate RIP3-dependent necroptosis, 57,58 perhaps as a strategy for immune escape. In this regard, it should be noted that viruses also subvert pathways linked to ICD including caspase-8 activation, 59 endoplasmic reticulum stress, 60 autophagy, 61 and type-1 IFN responses. 62 Successful anticancer chemotherapeutic agents induce all these hallmarks of ICD, suggesting that they induce a sort of 'viral mimicry'.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, intratumoral CVB3 administration can prominently recruit cytolytic degranulation marker CD107a-mobilized NK cells and granulocytes, and mature DCs into the tumor bed ( Figure 1). 9,27 As pathogenic viruses have developed their strategies to subvert ecto-CRT and circumvent ICD induction, 109 it is noteworthy that CVB3 infection can induce ecto-CRT accompanied by other DAMPs. 9 Furthermore, we demonstrated that both NK cells and granulocytes substantially contributed to the CVB3-mediated antitumor efficacy as evidenced by in vivo depletion assays.…”
Section: Damps Induced By Infection With Oncolytic Virusesmentioning
confidence: 99%
“…During apoptosis, CALR translocates to the cell surface, where it acts as a signal to promote phagocytosis by surrounding cells (121). Viruses may disrupt this process in order to prevent destruction of the infected cell (122).…”
Section: Fig 3 Enriched Annotation Terms and Pathways Among The Hummentioning
confidence: 99%